Effects of whale watching on the activity budgets of humpback whales, Megaptera novaeangliae (Borowski, 1781), on a feeding ground. Issue 4 (14th May 2018) - Di Clemente, Jacopo; Christiansen, Fredrik; Pirotta, Enrico; Steckler, Dave; Wahlberg, Magnus; Pearson, Heidi Christine
Abstract: Whale watching can affect cetacean behaviour, and can in some cases lead to long‐term negative effects on survival and reproduction. The waters of Juneau (Alaska) represent a summer feeding ground for the Central North Pacific stock of humpback whales, Megaptera novaeangliae (Borowski, 1781). The recent dramatic expansion of the local whale‐watching industry has raised concerns over the potential negative impact of such activity on the whales. The aim of this study was to understand the impact of whale‐watching vessels on humpback whale behaviour in Juneau. From June to September 2015, land‐based observations were conducted to record whale behaviour in the presence and absence of vessels. Markov chains and model simulations showed that the presence of vessels was not associated with a reduction in the time spent feeding. Whales exhibited more surface‐active behaviour and travelled less in the presence of vessels. The lack of an overt response of feeding whales to whale‐watching disturbance could result from the importance of the Southeast Alaska study region as a feeding ground, which could make the whales less apt to interrupt feeding under disturbance; however, The high proportion of travelling observed may indicate that the study area represents a travelling corridor between other, localized feeding areas. The increase in surface‐active behaviour may represent a response to vessel presence that could potentially lead to energetic consequences. The large number of whale‐watching vessels operating could lead to the increased tolerance of whales towards whale‐watching activities. The lack of responses in this study may suggest that the reactions of whales are context specific, depending on their previous experience with vessels and their foraging behaviour, for example. Subtler negative effects could still occur, however, and a prolonged monitoring programme is required to assess less overt behavioural responses of whales over time.